PENGARUH KUALITAS PELAYANAN DAN RELIGIUSITAS TERHADAP MINAT NASABAH MENABUNG PADA PT BPRS AL-WASHLIYAH KRAKATAU MEDAN - Siti Juniar; Pani Akhiruddin Siregar (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2026)
This research proves the hypothesis of whether service quality (X1) and religiosity (X2) influential and significant to customers interest in saving at PT BPRS Al-Washliyah Krakatau Medan (Y). The research method used is quantitative data analysis. The primary data was obtained through the distribution of closed questionnaires and structured to 99 respondents who save at PT BPRS Al-Washliyah Krakatau Medan. This primary data was then processed using SPSS version 21 and regressed with multiple linear regression analysis. The results of this research show: (1) All statement items proposed are valid and reliable because the calculated r is above the table r; (2) All independent variable explain 38,10% of the variation in the dependent variable, while the remaining 61,90% is due to other reasons; (3) The regression model on the independent variable simultaneously influence the dependent variable so that the regression model of the independent variable can be used to predict the dependent variable; (4) Service quality (X1) and religiosity (X2) influential and significant to customers interest in saving at PT BPRS Al-Washliyah Krakatau Medan (Y). The results of this research prove the hypothesis accepting H1 and H2. The discussion shows that service quality and religiosity play an important role in increasing customers interest in saving at PT BPRS Al-Washliyah Krakatau Medan. Good service quality is able to enhance customer satisfaction and trust, while religiosity encourages customers perspective towards PT BPRS Al-Washliyah Krakatau Medan.